Effect of Baggase NaLS Surfactant Concentration to Increase Recovery Factor - Arinda Ristawati; Sugiatmo Kasmungin; Rini Setiati (Penerbitan Universitas Trisakti, 2019)
Surfactant flooding may increase oil recovery by lowering interfacial tension between oil and water. Bagasse is one of the organic materials which contain fairly high lignin, where lignin is the basic substance of making Natrium Lignosulfonate (NaLS) Surfactant. In this research, bagasse based surfactant was applied for surfactant flooding. The research was divided into two sections, namely: phase behavior test and NaLS Surfactant flooding where the water contained 70,000 ppm NaCl. Two surfactant concentrations which were used were 0.75% and 1.5% NaLS surfactant. Phase behavior tests were carried out to find the middle phase emulsion formation. Based on phase behavior test results, the percentage of emulsion volume for 0.75% and 1.5% NaLS is 13.75% and 8.75%, respectively. NaLS surfactant flooding was performed for to obtain the best recovery factor. FTIR equipment used determine recovery factor. The optimum condition was obtained at 0.75% NaLS surfactant concentration where the recovery factor was 4.4%.